1985
DOI: 10.1007/bf01733666
|View full text |Cite
|
Sign up to set email alerts
|

Mesocaval and distal splenorenal shunts: Effect on hepatic function, hepatic hemodynamics, and portal systemic encephalopathy

Abstract: The effect of the mesocaval interposition shunt (n = 12) and the distal splenorenal shunt (n = 9) on the wedged hepatic venous pressure, the estimated hepatic blood flow, quantitative hepatic function, and the rate of portal systemic encephalopathy was evaluated in 21 patients who had bled from esophageal varices. After mesocaval shunt the wedged hepatic venous pressure was significantly reduced by 42% (from 26 +/- 3 mm Hg to 15 +/- 5 mm Hg, P less than 0.001) compared to 16% only (from 25 +/- 3 mm Hg to 21 +/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
3
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
2
3
0
Order By: Relevance
“…The existence of portosystemic shunts, detected on abdominal CT scans, was the most relevant hepatic abnormality preceding AHD in our patients. This finding is in keeping with results from other studies in which a chronic hepatic encephalopathy was observed in patients with portosystemic shunts because of noncirrhotic liver diseases such as schistosomiasis [31] or congenital cystic fibrosis [29], or conditions not involving hepatic damage such as portal vein thrombosis [30] or surgical shunting [32,33].…”
Section: Discussionsupporting
confidence: 92%
“…The existence of portosystemic shunts, detected on abdominal CT scans, was the most relevant hepatic abnormality preceding AHD in our patients. This finding is in keeping with results from other studies in which a chronic hepatic encephalopathy was observed in patients with portosystemic shunts because of noncirrhotic liver diseases such as schistosomiasis [31] or congenital cystic fibrosis [29], or conditions not involving hepatic damage such as portal vein thrombosis [30] or surgical shunting [32,33].…”
Section: Discussionsupporting
confidence: 92%
“…The findings of serum BCAA level changes in the present study correlate to some extent with those of Herz et al (31) where patients operated with shunt displayed a more pronounced reduction of the three BCAA after MIS than after DSRS. The latter group in their study had a better preserved hepatopetal portal flow, compared to our MIS patients who all had a reversed portal flow after 24 months of follow-up.…”
Section: Amino Acidssupporting
confidence: 92%
“…In this situation where the portal inflow is negligible or absent, the arterial flow and flow direction determine the EHBF. In most patients, the increase in arterial flow will not fully compensate for the reduction or loss of the portal flow [1,34,35]. Unfortunately, the magnitude of the decrease in EHBF after a shunt cannot be predicted since neither the increase in arterial flow nor the proportion of arterioportal 'steal' can be measured in advance of the operation or in tervention.…”
Section: Discussionmentioning
confidence: 99%